Estimation the Level of Follicular Fluid Follistatin in Women Undergoing Intracytoplasmic Sperm Injection (Medico Legal Update, 2020)
Objectives: A prospective study carried out in Kirkuk city from 15th of January 2019 to 10th of April 2019 , included 45 women who were enrolled in assisted reproductive technology (ART) programs in infertility Centre /Kirkuk, Iraq. Patients and method: All women were subjected to the basic fertility work-up at the infertility center which consists of history taking,physical examination, ovulation detection, evaluation of tubal patency and uterine cavity . The average age of the included women ranged between 20 and 42 years old. All women were enrolled in short protocol type of IVF/ICSI cycle and they had normal menstrual cycles. Nearly 5 ml of follicular fluid was obtained from all women undergoing ICSI for estimation of follistatin level by ELISA technique. Results : The present study showed that 31.1% (14 of 45) of women underwent ISCI technique became pregnant and 68.9% were non-pregnant (31of 45). The highest mean of age were recorded among pregnant women compared with non-pregnant women (32.21± 6.68 v.s31.80±5.38 year) although the result was non-significant (P: > 0.05). The highest mean of BMI were recorded among non-pregnant women compared with pregnant women (23.92 ± 1.55 v.s 25.36±1.99 kg/m2), the result was significant. The highest mean level of follicular fluid follistatin evaluated in pregnant compared with non pregnant (10.20±0.30 v.s 9.83±0.58 ng/ml) although the result was high significant difference (p: < 0.05). The study showed that there was negative correlation of follicular fluid follistatin level with age in pregnant women (r= -0.3), with positive correlation of with age in non-pregnant women. Conclusions: There was a highly significant relation of follicular fluid follistatin with pregnancy outcomes after ICSI.